Performance Analysis of CSMA/CA Based on D2D Communication - Abdulrazzak, Hazem Noori; Hussein, Aya Ayad (International Journal of Computer Sciences and Engineering, 2019)
This paper offers a complete idea and information about carrier sense multiple access with collisionavoidance (CSMA/CA) protocol. Firstly, what is the carrier sense multiple access protocol? and what is his job? Secondly, what is the collisionavoidance technique? and What is the effect of adding this technique to such protocol? Thirdly, knowing how to model an exact analysis to describe the protocol with it is techniques and the performance of the multiple random access method with ppersistent carrier sense multiple access and with collisionavoidance (CSMA/CA) protocol for highspeed and realizing fullydistributed (D2D) device to device communication based on IEEE 802.15.4. The collisionavoidance portion of CSMA/CA in this model is performed with a random pulse transmission procedure, in which a user with a packet ready to transmit initially sends some pulse signals with random intervals within a collisionavoidance period before transmitting the packet to verify a clear channel. The system model consists of a finite number of users to efficiently share a common channel. The time axis is slotted, and a time frame has a large number of slots and includes two parts: the collisionavoidance period and the packettransmission period. A discretetime Markov process is used to model the system operation. Also, it will be described by it is transmission state.